Individual names given to talking-gongs in the Yalemba area of Belgian Congo - Carrington, John F. (International Library of African Music, 1956)
The practice of giving individual names to talking-gongs has been reported for some central African tribes but is not known among all peoples using this musical instrument. It has been found to be common in the Yalemba area of Belgian Congo (Basoko territory, Oriental province) among groups using the gong-language known as (h?) So based on the spoken language of the (ba)So tribe. The following article is an attempt to put on record some of these instrumental names while at the same time recording measurements of gongs made in the field.
Keywords: Talking drum; Ethnomusicology; Percussion instruments; Drum; Drum language; Musical instruments; Talking-gongs; Idiophones; Belgian Congo; African Music; Drum (Instrument); Talking Drum (Instrument)